Identification of key Variables for the Development of Heritage Tourism in Denpasar City based on Sustainable Culture and Environment: Micmac Analysis - Anak Agung Gede Ngurah Manik Dirgayusa; Ni Putu Tirka Widanti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study aims to identify key variables influencing the development of heritage tourism in Denpasar City based on sustainable cultural and environmental principles. Denpasar, as the cultural heart of Bali, faces challenges in balancing urban modernization and cultural preservation. Using a qualitative descriptive approach supported by the MICMAC (Matrice d’Impacts Croisés Multiplication Appliquée à un Classement) method, this study maps the relationships and dependencies among twelve strategic variables gathered from literature studies and expert judgments involving academics, cultural leaders, and local government representatives. The analysis shows that zoning regulations and heritage protection policies (REG_ZONING) and stakeholder participation (STAKE_GOV) are the main driving variables shaping the sustainability of Denpasar’s heritage tourism. Meanwhile, variables such as pedestrian infrastructure, public transport integration, and creative economy vitality act as linkage variables, connecting policy with community-level implementation. The results indicate that sustainable heritage tourism in Denpasar can be achieved through integrated spatial regulation, collaborative governance, and local cultural revitalization rooted in the Tri Hita Karana philosophy. Keywords: Denpasar, Heritage Tourism, MICMAC, Sustainable Culture, Tri Hita Karana.